KINERJA PEGAWAI DALAM PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) DI DINAS PEKERJAAN UMUM KABUPATEN SANGGAU - Dian Yanuar E.42009015 (FISIP Universitas Tanjungpura Pontianak, 2022)
This essay made to knowing about official Government performance in Dinas Pekerjaan Umum Sanggau Regency while they gave serve the building permits to peoples who need this permit from responsiveness aspect, responsibility aspect and accountability aspect. The point of this problem in this research was how the official performance in Dinas Pelayanan Umum serving the building permits.This research using descriptive method with qualitative type. The conclusion of this research show that official government performance in Dinas Pekerjaan Umum Sanggau Regency from responsiveness and responsibility aspects was still very low, it was proved from service time uncertainty, the official gave less responsive against peoples complaints, service information very slow and less official in the service building permits. At the same time, from responsibility aspect was good enough, it was showed that the official government has worked in accordance with the procedure and mechanism that has set in the agency of building permits management, the weakness that the official still can’t gave the fast and right service to peoples. Keywords : Performance, Official Government, Service